Tipping the scales: ambidexterity practices on e-HRM projects. Issue 4 (27th May 2014) - Tansley, Carole; Kirk, Susan; Williams, Hazel; Barton, Harry
Abstract : Purpose: – The purpose of this paper is to examine and conceptualise the ways in which a balance can be achieved between optimising the efficiency and effectiveness of electronic human resource management (e-HRM) systems for human resource management (HRM) and enabling innovation to occur during the system implementation. Design/methodology/approach: – An interpretive case study of a UK local authority e-HRM system implementation is examined using the notion of ambidexterity as an analytical device. Ambidexterity relates to how an organisation develops the ability to operate efficiently in the now, while at the same time being able to adapt to environmental changes around and ahead of them in order to grow into the future. Findings: – As an intra-organisational capability, ambidexterity is found to derive from the simultaneous interplay and balancing of dual capabilities: exploitation and exploration. e-HRM exploitation concerned the capability to generate new knowledge with innovatory effects, created through the everyday practices performed by practitioners at all levels in the organisation. e-HRM exploration, rather than being a purposeful act, was found to be an accidental consequence of engaging in exploitation to maintain the status quo. Research limitations/implications: – The notion of ambidexterity was originally constructed within strategic management and studies in the field have previously been confined to this area. This makes this study theoretically and empirically experimental, making it a challenging research endeavour. Another limitation is that the authors only sought views from the interviewees on how external forces might limit or facilitate their ambidexterity, as opposed to actually studying those forces themselves. Practical implications: – The authors suggest that those in organisations who are responsible for strategic HRM need to consider ways in which "intentional" opportunities for ambidexterity in e-HRM systems implementation can be identified and harnessed to ensure better balances between exploitation and exploration in such endeavours and to guard against innovation only occurring through chance. Originality/value: – There is a lack of detailed investigation of how organisations actually achieve ambidexterity, particularly in three under-researched areas: ambidexterity in the public sector, at human resourcing functional level and e-HRM systems implementation. Bundling these three areas into an integrated examination allows us to both identify how exploitation and exploration play out in the ambidextrous practices of an e-HRM project and also to identify the dimensions of ambidexterity in balancing e-HRM work.